Sustainable Marketing Strategic Planning in Pharma and Internet of things as Part of the New Circular Economy - Raluca CONSTANTINESCU; Ada O. MIRCEA; Denisa R. MUNTEAN (Communications of International Proceedings, 2022)
The United Nations has identified 17 sustainability goals which are currently part of the 2030 Agenda for Sustainable Development (United Nations, 2015). The struggle to end poverty and other deprivation must be accompanied by strategies to improve health and education, reduce inequality, and promote economic growth, while confronting climate change and protecting the currently available natural resources we have. As Kumar et al. (2020) noted, COVID-19 provides space for the development of flexible and robust manufacturing systems to maintain the economic and social viability of production processes. This paper aims to conceptually study and define based on the analysis, the relationship between pharma industry and Internet of Things concept, in terms of sustainable marketing strategic planning. In the marketing segment, strategic planning can be questioned as “How sustainability could be integrated in the pharma industry worldwide” and “What will be the impact in a world defined by the Internet of Things in the future”.
Keywords: circular economy; pharma; internet of things; sustainability; strategic planning; marketing.